Assessment of Screen Time with its Effect on Health among Secondary School Students - Rahman, Md Sohanur; Roy, Biplab Kumar; Nazneen, Nazia; Molla, Md Shahin; Suvo, Sohanur Rahman (Mediscope, 2024)
Background: Secondary school students are more and more immersed in a world dominated by screens in the modern digital era. Screens, ranging from laptops to tablets, televisions to smartphones, have embedded themselves into daily life and significantly impact how youngsters communicate, learn, and pass the time. Objective: The study's objective was to find out the assessment of screen time and its effect on health among rural secondary school students in Bangladesh. Methods: This cross-sectional descriptive type of study was carried out in Govt. Jalma Chakrakhali Secondary School in Batiaghata Upazilla under Khulna district. A total of 460 students were selected using a convenient sampling technique from a selected school in Khulna district. Face-to-face interviews with a semi-structured questionnaire were used to collect data. Data were analyzed following the study's objectives. Before data collection, informed consent was taken, and ethical concerns were addressed at different stages of the study. Results: Among 460 respondents, a large number 52% (241) were between 14-16 years of age group. Only 38% had a personal mobile phone, while where a maximum (72%) used their parents' phones. Male students (76%) had a greater tendency to operate mobile phones in comparison to females (64%). Among the parents, most of them (82%) had a smartphone. Most of the respondents [395 (86%)] had a TV at their house and 304 (66%) watched TV regularly. Almost half of the respondents [223(48%)] suffered from various health issues, where headaches and blurring of vision were the main features. Conclusion: This study painted a clear picture of the effect of screen time on Bangladeshi rural school-going youngsters, and it may be able to assist the relevant authorities in developing policies and formulating plans to address the issue. Mediscope 2024;11(2): 82-86